2020
DOI: 10.1101/2020.08.30.20184598
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Uncertain COVID-19 Spread Pattern in India: A Statistical Analysis of the Current Situation

Abstract: There are standard techniques of forecasting the spread of pandemics. Uncertainty however is always associated with such forecasts. In this article, we are going to discuss the uncertain situation currently prevailing in the COVID-19 spread in India. For statistical analysis, we have considered the total number of cases for 60 consecutive days, from June 23 to August 21. We have seen that instead of taking data of all 60 days together, a better picture of uncertainty can be observed if we consider the data sep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…It was seen that [8] during June 1 to June 9 it became 0.04063. When the matter was studied with data for 60 consecutive days [9], from June 23 to July 12, the average value of Δ z ( t ) was 0.034576, from July 13 to August 1 it was 0.034458, and from August 2 to August 21 it was 0.026449. So we have seen that as time progressed, the values of Δ z ( t ) were reducing.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was seen that [8] during June 1 to June 9 it became 0.04063. When the matter was studied with data for 60 consecutive days [9], from June 23 to July 12, the average value of Δ z ( t ) was 0.034576, from July 13 to August 1 it was 0.034458, and from August 2 to August 21 it was 0.026449. So we have seen that as time progressed, the values of Δ z ( t ) were reducing.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…It was observed [5, 6, 7, 8, 9] that from Δ z ( t ) we can extract an important information. When the pandemic continues to grow exponentially, Δ z ( t ) would continue to decrease linearly in time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, during the sub-exponential stage of growth of COVID-19, Δ z ( t ) was observed to have followed a decreasing trend. It was shown in [11] that from June 23 to August 21, in India Δ z ( t ) had followed the following three linear equations established using the method of least squares. The study was made for 60 days, separated into three equal parts of 20 days each.…”
Section: Methodsmentioning
confidence: 99%
“…It was statistically concluded that during the first 20 days the coefficient of regression of Δ z ( t ) on t was negative, during the next 20 days it was insignificant and in the last 20 days the regression coefficient was negative again. Using the equation fitted from data from August 2 to August 21, a forecast was made in [11] that starting from August 2, within no more than 78 days retardation would start in India. That forecast could be seen to be true.…”
Section: Methodsmentioning
confidence: 99%